Gastrointestinal Stromal Tumor of the Stomach Presenting as a Perigastric Abscess - Dong Ryul Kim; Jee Young An; Soo Jeong Han; Hyungkeun Kim; Seoree Kim; Jiyeon Yoo; Seung Hyun Oh; Chung Min Han; Jung Hwan Oh (Yong Chan Lee, 2017)
Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. A 77-year-old man was referred for the evaluation of general weakness and leukocytosis. Computed tomography showed a 9.5×6.5-cm cavitary lesion with an air-fluid level near the stomach, which was thought to be a perigastric abscess. Upper endoscopy revealed a fistula on the greater curvature at the mid body of the stomach. The margin of the fistula opening was clearly demarcated, and yellow turbid fluid oozing from the fistula was seen. Laparoscopic wedge resection was performed at the perforated area of the stomach. Immunohistochemistry revealed CD117 expression. A diagnosis of intermediate-risk GIST was made. No recurrence was identified within 18 months after the operation. The final diagnosis was perforated gastric GIST communicating with the gastric lumen and presenting as an intra-abdominal abscess.